One Interval Does Not Fit All: A Comment on "Optimizing Post-Activation Performance Enhancement in Athletic Tasks: A Systematic Review with Meta-Analysis For Prescription Variables and Research Methods"...Xu K, Blazevich AJ, Boullosa D, et al. Sports Medicine. 2025;55(4):977-1008. - Lima, Leonardo C. R.; Fontanetti, Gabriel (Sports Medicine, 2025)
The letter provides insights on a review article discussing post-activation performance enhancement (PAPE) and commends the authors for their comprehensive frameworks. It highlights two key aspects: the need for specific recovery intervals between verification tests based on the nature of the test, and the potential effectiveness of a self-selected interval method for optimizing rest periods in elite athletes. The authors advocate for further research into these areas to enhance the understanding and application of PAPE in athletic settings.